World market access of emerging-market firms: The role of foreign ownership and access to external finance - Horst Raff; Natalia Trofimenko (Kiel Institute for the World Economy (IfW), 2013)
This paper uses micro-data from the World Bank Investment Climate Surveys 2002-2006 to investigate how foreign ownership and access to external finance affect the likelihood of manufacturers in emerging markets to export and/or import. Applying propensity score matching to control for differences across firms in terms of labor productivity, size, etc., we find that foreign ownership and access to external finance are statistically significant determinants of the likelihood that a firm will export or import. Foreign ownership has a large positive impact on the likelihood to engage in direct trade but a negative effect on the likelihood to trade through intermediaries; the effects vary across upper and lower middle income countries. Access to external finance has a modest but positive effect on the likelihood to engage in any of the modes of connecting with foreign customers or suppliers.
Keywords: F12; F14; F23; O19; 330; international trade; foreign ownership; financing; developing countries; intermediation; multinational enterprise